Computer-assisted instruction to Index to Philippine Periodicals - Lumague, Blythe M.; Cruz, Ma. Divina P. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
The main concern of this study is to create an alternative tool to render an end-user database national instructions. The program developed through the use of MS Office Power Point (Windows 97). It takes 16 minutes to view the five modules plus the introduction. The CASI is created following four useful steps: stating the objectives, designing the presentation, writing the program, testing and revising the program.
To test the CAI to IPP, fifty respondents were chosen based in convenience/Incidental sampling wherein the respondents were approached individually until the desired sample size was reached. The evaluation of the proposed CAI was done for one week starting March 21 to March 26, 1999 using the two computer terminals at the General Reference Section of the UP Diliman Main Library. After the respondents have viewed the computer-assisted instruction program, their feedback was recorded using a questionnaire.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Computer-assisted instruction -- Authoring programs; Index to Philippine Periodicals